ANALISIS KEUNGGULAN BERSAING IKAN ASAP TUNACA DI KOTA AMBON - Eva M Jadera; Yolanda MTN Apituley; Renoldy Lamberty Papilaya (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2017)
This research aims to describe the characteristics of respondents, identify levels of statisfaction and expectations of consumers and analyzing the competitive advantage smoked fish Tunaca, this research is done in the processing and marketing of products by applying methods of surveying using a detailed questionnaire and interview as a means of collecting the data of principal. The sample as many as 50 people are determined based on techniques AccidentalSampling that is a consumer who buys smoked fish is found Tunaca. The analysis used is descriptive qualitative analysis and qualitative analysis in quantitative with application of likert scale. The research result to describecharacteristics of respondents based on age, gender, education, occupation, income and the number of family members. The purpose of the following indicate statisfaction and expectations of consumers against variables, variables that are consigered to have a competitive advantage of smoked fish product is durability, taste, halal and packaging product.